N[sub 2]O formation in combustion systems - United States. Department of Energy. (Fossil Energy Research Corp., Laguna Hills, CA (United States), 1990)
The objective of this project is to characterize N[sub 2]O emissions from combustion sources emphasizing N[sub 2]O emissions from post-combustion selective gas phase NO[sub x] reduction processes and reburning. The processes to be evaluated include selective noncatalytic NO[sub x] control (ammonia, urea and cyanuric acid injection), and reburning. The project includes pilot-scale testing at two facilities supported by chemical kinetic modeling. Testing is being performed on both a gas-fired plug flow combustor and a pulverized-coal fired combustor. Work performed to date has included the performance of the initial detailed chemical kinetics calculations. These calculations showed that both urea and cyanuric acid produce significant quantities of N[sub 2]O, while NH[sub 3] injection produced negligible amounts, These kinetics data support limited test results reported for cyanuric acid and ammonia injection. Laboratory work to evaluate the selective gas phase NO[sub x] reduction processes listed above has begun. Testing to evaluate reburning at the coal-fired facility is being performed in parallel with the testing at the gas-fired facility. Following completion of the test work, additional kinetics calculations will be performed.